Early arthritis as a rheumatological chameleon: a description of a clinical case - E. A. Galushko; A. V. Alekseeva; G. V. Serikova; A. S. Semashko (Современная ревматология, 2021)
The article discusses the difficulties of differential diagnosis of early arthritis and inflammatory bowel diseases with a predominant clinical picture of extraintestinal manifestations, in particular, articular syndrome. The clinical observation demonstrates features of the course of such conditions, a long diagnostic search and a wide list of diseases included in differential diagnostics range.